Hepatic insulin clearance is increased in patients with high HbA1c type 2 diabetes: a preliminary report. Issue 1 (29th April 2020) - Okura, Tsuyoshi; Fujioka, Yohei; Nakamura, Risa; Anno, Mari; Ito, Yuichi; Kitao, Sonoko; Matsumoto, Kazuhisa; Shoji, Kyoko; Sumi, Keisuke; Matsuzawa, Kazuhiko; Izawa, Shoichiro; Okura, Hiroko; et al.
Abstract : Introduction: Hepatic insulin clearance (HIC) is an important pathophysiology of type 2 diabetes. HIC was reported to decrease in patients with type 2 diabetes and metabolic syndrome. However, hyperglycemia was suggested to enhance HIC, and it is not known whether poorly controlled diabetes increases HIC in patients with type 2 diabetes. We investigated whether HIC was increased in patients with poorly controlled diabetes, and whether HIC was associated with insulin resistance and incretins. Research design and methods: We performed a meal tolerance test and the hyperinsulinemic–euglycemic clamp in 21 patients with type 2 diabetes. We calculated the postprandial C-peptide area under the curve (AUC)-to-insulin AUC ratio as the HIC; measured fasting and postprandial glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) and glucagon levels and analyzed serum adiponectin and zinc transporter-8 (ZnT8) gene polymorphism. Results: The HIC significantly correlated with glycated hemoglobin (HbA1c) ( r_S =0.58, p<0.01). In patients with high HIC above the median of 6.5, the mean HbA1c was significantly higher compared with low HIC below the median. Homeostatic model assessment (HOMA)-beta ( r_S =−0.77, p<0.01) and HOMA-IR ( r_S =−0.66, p<0.005) were correlated with HIC. The M/I value in the clamp study was correlated with HIC. GLP-1-AUC and GIP-AUC were not correlated with HIC. Glucagon-AUC was negatively correlated with HIC, but there were no significant differences between the high and low HIC groups. Adiponectin was positively correlated with HIC. The ZnT8 gene polymorphism did not affect HIC. Conclusions: These results suggest that HIC was increased in patients with high HbA1c type 2 diabetes, low insulin secretion, low insulin resistance and high adiponectin conditions.